The Stability of Slopes Subjected to Blasting Vibration-Assessment and Application in Hong Kong - R Law; R Keller (International Society of Explosives Engineers, 1996)
In the rush to beat the clock before the handover of Hong Kong back to China in June of 1997, an unprecedented amount of infrastructure work is being undertaken at a breakneck pace. In the middle of this construction explosion, on this island of barren granite , stands some of the most concerning and restrictive slope stability measures. So conservative, these measures impact blasting and vibration control to an extent unmatched anywhere in the world.